2022
DOI: 10.21203/rs.3.rs-1609217/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping of Livestock Value Chains as a Tool for Understanding Disease Risks in Agro-Pastoral Systems of Kajiado County, Kenya

Abstract: BACKGROUND Ruminant production plays a major role in the Kenyan livestock sector, but they face a myriad of disease threats including zoonoses. The objective of this study was to map the ruminant livestock value chains and describe disease risks and their implication to pastoral livelihoods in Kajiado South sub-county, Kenya. This area is characterised by a highly intertwined wildlife-livestock-human interface which is ideal for transmission of zoonoses and other livestock diseases to connected systems and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that there is misuse of antibiotics among livestock keepers in Africa and that this could fuel the development of antimicrobial resistance [ 12 , 35 ]. Limited access to veterinary services, reliance on friends and past experiences in determining treatment and easy access of drugs in the villages have been identified as some of the reasons why pastoralists self-medicate their livestock [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that there is misuse of antibiotics among livestock keepers in Africa and that this could fuel the development of antimicrobial resistance [ 12 , 35 ]. Limited access to veterinary services, reliance on friends and past experiences in determining treatment and easy access of drugs in the villages have been identified as some of the reasons why pastoralists self-medicate their livestock [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%